Religious Moderation Representation in The Movie "My Name is Khan" - Jamilatun Nafi'ah (FALASIFA : Jurnal Studi Keislaman, 2022)
This discussion will examine more deeply the forms of religious moderation represented in the film "My Name Is Khan". This is intended to get a clear picture of how to apply religious moderation and its limits in diversity. Religious diversity is a natural trait that cannot be denied. However, how through this moderation can such diversity be accepted and remain peacefully side by side. The figure of Rizvan Khan who is the main character in the film "my name is khan" has displayed a Muslim character with his moderate attitude towards fellow human beings. His struggle to save non-Muslims who were being hit by storms and floods in Wilhelmina, Georgia to firmly fight the heretical teachings of Islamic terrorism who wanted to provoke other Muslim worshipers in a mosque. The film conveys a brief message that religion is not a differentiator that divides people. And Islam is not a religion of cruelty and terrorism, but Islam is a religion that can embrace diversity in moderation. The storyline is so full of conflict and Islamic studies that are quite heavy can be packaged lightly and can be enjoyed by the audience of the film My Name is Khan. The positive side of this film that we can take is how we as individuals must always try to continue to be good people because in this world there are only good people and bad people. To whom we must do good, regardless of race, religion, nation, and skin. And to complete it, we must always have a good attitude towards other people, whether they are Muslims or non-Muslims though.